Large‐scale gene expression reveals different adaptations of Hyalopterus persikonus to winter and summer host plants. (25th May 2016) - Cui, Na; Yang, Peng-Cheng; Guo, Kun; Kang, Le; Cui, Feng
Abstract: Host alternation, an obligatory seasonal shifting between host plants of distant genetic relationship, has had significant consequences for the diversification and success of the superfamily of aphids. However, the underlying molecular mechanism remains unclear. In this study, the molecular mechanism of host alternation was explored through a large‐scale gene expression analysis of the mealy aphid Hyalopterus persikonus on winter and summer host plants. More than four times as many unigenes of the mealy aphid were significantly upregulated on summer host Phragmites australis than on winter host Rosaceae plants. In order to identify gene candidates related to host alternation, the differentially expressed unigenes of H. persikonus were compared to salivary gland expressed genes and secretome of Acyrthosiphon pisum . Genes involved in ribosome and oxidative phosphorylation and with molecular functions of heme–copper terminal oxidase activity, hydrolase activity and ribosome binding were potentially upregulated in salivary glands of H. persikonus on the summer host. Putative secretory proteins, such as detoxification enzymes (carboxylesterases and cytochrome P450s), antioxidant enzymes (peroxidase and superoxide dismutase), glutathione peroxidase, glucose dehydrogenase, angiotensin‐converting enzyme, cadherin, and calreticulin, were highly expressed in H. persikonus on the summer host, while a SCP GAPR‐1‐like family protein and a salivary sheath protein were highly expressed in the aphids on winter hosts. These results shed light on phenotypic plasticity in host utilization and seasonal adaptation of aphids.